2020
DOI: 10.1371/journal.pgen.1008645
|View full text |Cite
|
Sign up to set email alerts
|

The conserved regulatory basis of mRNA contributions to the early Drosophila embryo differs between the maternal and zygotic genomes

Abstract: The gene products that drive early development are critical for setting up developmental trajectories in all animals. The earliest stages of development are fueled by maternally provided mRNAs until the zygote can take over transcription of its own genome. In early development, both maternally deposited and zygotically transcribed gene products have been well characterized in model systems. Previously, we demonstrated that across the genus Drosophila, maternal and zygotic mRNAs are largely conserved but also s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 91 publications
3
8
1
Order By: Relevance
“…M1BP is involved in transcriptional regulation and RNA polymerase II pausing at the promoter of genes ( Li and Gilmour 2013 ), which may also be associated with regulating chromatin state ( Ramírez et al 2018 ). Our findings are consistent with previous studies that identified the enrichment of binding sites for M1BP, BEAF-32, and Dref in the promoter regions of genes that are maternally deposited ( Chen et al 2013 ; Omura and Lott 2020 ). These binding sites have also been associated with housekeeping genes ( Zabidi et al 2015 ), and the pool of maternal transcripts is enriched with housekeeping genes ( Liu et al 2014 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…M1BP is involved in transcriptional regulation and RNA polymerase II pausing at the promoter of genes ( Li and Gilmour 2013 ), which may also be associated with regulating chromatin state ( Ramírez et al 2018 ). Our findings are consistent with previous studies that identified the enrichment of binding sites for M1BP, BEAF-32, and Dref in the promoter regions of genes that are maternally deposited ( Chen et al 2013 ; Omura and Lott 2020 ). These binding sites have also been associated with housekeeping genes ( Zabidi et al 2015 ), and the pool of maternal transcripts is enriched with housekeeping genes ( Liu et al 2014 ).…”
Section: Resultssupporting
confidence: 93%
“…The oocyte itself is thought to be largely transcriptionally silent ( Navarro-Costa et al 2016 ). What we found here, and what was also found in another study investigating binding motifs in maternal factors across the Drosophila genus using computational methods ( Omura and Lott 2020 ), is that maternal transcription is associated with trans factors annotated to be insulators and that interact with TADs. This provides evidence that maternal transcription may be controlled broadly at the level of chromatin state.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations